Systematic computer analysis of published literature on nutritional support for vaccination - A. G. Chuchalin; I. Yu. Torshin; O. A. Gromova (Фармакоэкономика)
A range of 6700 publications from the PubMed database on the association of micronutrient supply and results of antibacterial and antiviral vaccination was reviewed by the method of topologic and metric analysis. This method allows for a selection of features (i.e. key words) by their informativity, the establishment of the most informative that provide the basis for “synthetic” features and algorithms, or the classification of the reviewed text by the relevance to the subject of the study. The results of fundamental studies showed that folates, vitamins A, D, and B12 are the regulators of mitosis of T and B-lymphocytes that exert the functions of the acquired immunity. Such microelements as zinc, iron, selenium, manganese, and omega-3 polyunsaturated fatty acid support the functioning of T and B-lymphocytes (energy metabolism, intracellular signal transmission, and transcription). Clinical studies showed that the support of vaccination with the specified micronutrients not only increases the titre of the respective antibodies to viral and bacterial pathogens but can also prevent unfavorable effects from vaccination. The administration of micronutrients before and after vaccination will contribute to a decrease in the mortality rate and severity of the pathology development (in case of disease). A systematic analysis allowed the authors to determine the perspectives of the proposed measures for an increase in the effectiveness and safety of vaccines, including COVID-19. Additional micronutrient supply contributes to an increase in the effectiveness and safety of vaccination. The application of specialized vitamin and mineral complexes during vaccination is economically feasible and reduces the vaccination risks for patients with polyhypoavitaminoses.